Bentuk Kesantunan dalam Tuturan Masyarakat Melayu Jambi di Desa Jumbak: Studi Pragmatik - Lini, Saplini; Akhyaruddin, Akhyaruddin; Saputra, Ade Bayu; Purba, Andiopenta (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to describe the forms of politeness in the utterances of the Malay Jambi-speaking community in Jumbak Village, Jujuhan Subdistrict, Bungo Regency. This research employs a qualitative approach with a descriptive pragmatic method. Data were collected through uninvolved conversational observation, recording, and note-taking techniques during natural interactions in various contexts such as homes, markets, and traditional events. The findings reveal 31 utterances representing 17 forms of politeness. These forms were analyzed using the theories of Leech (1983), Grice (1975), and Brown & Levinson (1987), which include politeness maxims, the cooperative principle, and strategies of positive and negative politeness. The study shows that the use of politeness in the Malay Jambi language reflects the cultural values and social norms of the local community. This linguistic politeness serves to maintain social harmony and is a vital part of cultural and linguistic preservation. The study contributes to the development of local pragmatic studies and may serve as a reference in language and regional culture education, particularly in integrating local values into communicative competence. Keywords: Forms of politeness, Malay Jambi language, Pragmatic study